PERENCANAAN TATARUANG PESISIR KOTA AGUNG BERBASIS ANALSIS RISIKO BENCANA TSUNAMI - wisyanto, wisyanto (Badan Pengkajian dan Penerapan Teknologi, 2009)
Gradually, the land that can be cultivated or used will lessen, moreover in a city that is growing rapidly. The situation has forced local government to plan the use of any land conscientiously. Formerly, local government plans the land just for beautifulness of a city and for practicality of transportation system without consideration of natural disaster mitigation. Natural disasters have damaged social and economic infrastructure and also killed people of many regions. The long term consequences of natural disasters are especially severe for developing countries and hamper the achievement of their sustainable development. Spatial planning that based on disaster mitigation has been done in The Coast of Kota Agung. The planning has been made through evaluation of the existing city planning by comparing it with the result of tsunami risk analysis. From the tsunami risk analysis, it has been known the volume of potential losses of threatened object per area units in the Coast of Kota Agung. By knowing their vulnerability and the level of risk, we have improved the existing city planning. It is hoped that the city planning that based on disaster risk analysis would make Kota Agung to be a city that will develop properly and safer from tsunami threatening.